1982
DOI: 10.1002/ajim.4700030205
|View full text |Cite
|
Sign up to set email alerts
|

Malignant pericardial mesotheliomas and asbestos exposure: A case report

Abstract: Three cases of malignant pericardial mesotheliomas are presented with evidence of occupational asbestos exposure. Examination results are compared with findings from experimental and epidemiological research on biological effects of asbestos dust. There are sufficient indications that time-limited effects of asbestos dust established either by measurements or assessment of the amount of concentration after a latency of more than 20 years are apt to result in the development of mesotheliomas of the pleura and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

1986
1986
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…Thomason et al reported that exposure to asbestos had been documented in four of 28 cases (14%) 1) . Beck et al reported three cases of primary pericardial mesothelioma associated with occupational asbestos exposure 9) . In Japan, Kishimoto, et al reported a female case of pericardial mesothelioma who had been working in Navy dockyard, and found asbestos bodies in her lung 10) .…”
mentioning
confidence: 99%
“…Thomason et al reported that exposure to asbestos had been documented in four of 28 cases (14%) 1) . Beck et al reported three cases of primary pericardial mesothelioma associated with occupational asbestos exposure 9) . In Japan, Kishimoto, et al reported a female case of pericardial mesothelioma who had been working in Navy dockyard, and found asbestos bodies in her lung 10) .…”
mentioning
confidence: 99%
“…In the present study, clinical and echocardiographic features of constrictive pericarditis were not present in any patient but in 45% of patients pericardial involvement in the form of pericardial thickening, pericardial effusion and pericardial calcification was detected. In the literature, more than 140 patients with primary malignant pericardial mesothelioma were reported 16,17 . However, in our clinic we have not seen any patient with primary malignant pericardial mesothelioma.…”
Section: Discussionmentioning
confidence: 64%
“…In the literature, more than 140 patients with primary malignant pericardial mesothelioma were reported. 16,17 However, in our clinic we have not seen any patient with primary malignant pericardial mesothelioma.…”
Section: Discussionmentioning
confidence: 87%
“…[36–10] The role of asbestos exposure is not clear, although it has been documented in a few patients. [3910] The clinical course of the disease is often rapid and the mean survival time from onset of symptoms to death is 5–8 months for the sarcomatous variant and 6–8 months for the biphasic variant. [4610] Cardiac tamponade is a well-known complication of the malignancy and often responds initially to pericardiocentesis or to pericardial window,[10] but some fatal cases have been reported.…”
Section: Discussionmentioning
confidence: 99%